Nghiên cứu cấu trúc kì hạn nợ của công ty tại Việt Nam - Trần Thị Thùy, Linh; Nguyễn Thanh, Nhã (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
The primary aim of this study is to examine the impacts of various factors on the maturity structure of corporate debt, i.e. the effects of external and internal factors on the debt maturity structure of the enterprises listed on Hochiminh Stock Exchange (HOSE) between 2007 and 2015. By using system GMM technique, we find that debt maturity are influenced by such variables as size, growth opportunities, debt ratio, liquidity, earnings volatility, and tangible assets (as an internal factor tangible assets are found to have the most profound impact on firm’s debt maturity structure). In addition, Vietnamese firms take on more long-term debt during an increase in the difference between returns of the government bond and treasury note when growth opportunities seem to be better for more corporate investment.